Pharmacological treatment for Continuous spike‐wave during Slow Wave Sleep and Landau‐Kleffner Syndrome - Moresco, Luca (Cochrane Database Syst Rev, 2018)
This is a protocol for a Cochrane Review (Intervention). The objectives are as follows: To assess the efficacy and tolerability of pharmacological interventions for the treatment of CSWS and LKS.